Occupational noise exposure amongst road construction workers - Mohd. Said, Kamilah (2015)
Overexposure among construction workers to hazardous noise level may affect workers safety and health. The aim of this study is to determine the level of noise exposure among road construction workers. To achieve this aim, the sound power level of construction machineries, workers noise exposure level and the prevalence of hearing loss symptoms and hearing ability among them were measured. Sound power level of machineries were measured according to ISO 112000. The workers consist of operator of machineries, site supervisors and premix workers were measured according to Peraturan-Peraturan di bawah Akta Kilang dan Jentera 1967 (Akta 139) P.U. (A) 1/89 Factories and Machinery (Noise Exposure) Regulations 198. A total of seventy three workers who worked in road work, drainage and pavement stage were measured their noise exposure level. These workers also were evaluated their hearing loss symptoms and hearing ability using questionaire survey and interview. Machineries consisting of roller compacter, back-pusher, vibratory roller and paver have high sound power level. There are 44% of workers including operators, site supervisors and premix workers had experienced noise level above hazardous level (=85 dBA). Vibratory roller operator obtaining high exposure level with the highest exposure appeared in pavement stage. Highest prevalence symptoms of hearing loss was recorded in road work stage with 39% of workers positive hearing loss due to factors of workers’ age, racing and karaoke activity. Poor hearing ability were observed for workers with age of 60 years old and greater. It is suggested that workers exposed to noise greater than 85 dBA should wear hearing protection device (HPDs) with suitable NRR values. In conclusion, road construction workers also exposed to hazard which require them to wear hearing protection.